Implementasi Manajemen Mutu Pendidikan di Madrasah Swasta - Maulana, Agung; Dian, Dian; Jahari, Jaja (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2019)
Madrasa are in a condition of interrelated problems, including inadequate funding, inadequate facilities, modest teachers and attending more than one school, low quality, lack of enthusiasm, low innovation, and low interest. Madrasas do not yet have an internal quality assurance. This research aims to reveal the implementation of quality management in Madrasah Aliyah Nurul Iman Cimahi City, Indonesia. The research method uses a qualitative descriptive approach that is describing phenomena in the implementation of quality in private madrasas. Data collection techniques used interview studies with the headmaster, deputy headmaster and educators; documentation study relating to documents related to 8 standards in madrasas; observational studies namely the implementation of quality, internal quality assurance in madrasas. The results showed that the low quality of education in the madrasas had an impact on funding madrasas that still did not have financial independence, madrassas still relied on madrasah operational assistance and monthly fees from students. The academic quality assurance agenda is carried out maximally by the madrasah academic community.